Looking back : Hugh McKee's Stable (Raton Range Raton, NM, 1979)
This article is about Hugh McKee's stable.
Newspaper article + Photograph of Hugh McKee's Stable
Master list item #: 18
File location is in the Raton file Cabinet
Keywords: Mckee, Hugh; Rand, Kathleen; Hugh McKee's Stable; International State Bank; Building History; Business Building; Stables; Second Street -- Raton, New Mexico